Hippopotami in a liminal space: a multi-species ethnography of Lake Tanganyika in Bujumbura - Maksudi, Bakenga (Environmental Humanities South, 2023)
This thesis explores how human encroachment has significantly altered Lake Tanganyika's freshwater ecosystem and riparian zone in Bujumbura, the capital city of Burundi, which affects the daily life and interactions between humans and hippopotami (hippo). Societal development agendas have favoured economic growth and infrastructural development with little regard for the well-being of multi-species communities. The study contrasts the ideas that drive economy-based approaches to development and environmental management with the many engagements with the lake, and how this in turn affects human-hippo relations on Lake Tanganyika's riparian zone. Environmental protection and management discourses are frequently portrayed as a unified, single, objectivist practice, however, their contextual enactment differs from discipline to discipline and across municipal interventions and service delivery. The study investigates how the current settlement developments affect human-hippo relations. Specific research questions include, what are the intersecting human-hippo interactions that exist in Bujumbura's lakeshore neighbourhoods? What impacts do these interactions have on people and hippos? What interventions can help restore the degraded environment and foster kinship? I respond to these questions by engaging with current debates in environmental humanities, cultural, and environmental anthropology on human-multi-species entanglements. Both grounded theory and multi-species ethnography approaches were used as data collection and analytic tools in this study. I trace nutrient and energy flows to foreground the interdependencies between the “human world” and “natural world”, a separation that is no longer viable in the time of the Anthropocene. Triangulated data sets are used to narrate stories and critically discuss the current environmental challenges using ecocentric, and actor-network theory as the conceptual frameworks. Although population growth is considered a key factor in environmental degradation, I argue that the deterioration of the environment, particularly the coastal landscape, may be attributed to improper and unclear land-water management. The findings of this study indicate that land acquisition on the riparian zone for settlement development in the Gisyo and Kibenga is associated with power and affluence by some members of society. Potential land-water insights and spatial planning approaches for a human-and-hippo-friendly riparian zone are proposed.